Latency and Reliability Evaluation of an HTTP-Controlled ESP8266 Wi-Fi Robot Car Using MIT App Inventor - Ryan Fikri; Agariadne Dwinggo Samala; Thamrin Thamrin; Delsina Faiza (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Low-cost Wi-Fi robot cars are frequently presented as functional prototypes, but many studies do not quantify whether motion commands remain reliable and responsive as wireless distance increases. This study therefore designed and experimentally evaluated an ESP8266-based differential-drive robot controlled by an Android application developed with MIT App Inventor. The proposed solution applies an HTTP command-mapping method in which each mobile-interface event is converted into a request, parsed by an ESP8266 web server, mapped to an L298N H-bridge state, and acknowledged after the control action is issued. The objective was to determine functional command accuracy and characterize the relationship among control distance, command-response latency, received signal strength indicator (RSSI), and communication reliability. Five commands forward, backward, left, right, and stop were tested in 150 functional trials, while 500 communication trials were conducted at 1, 5, 10, 15, and 20 m under indoor line-of-sight conditions. The robot correctly executed 148 of 150 functional commands, corresponding to 98.67% success. Distance-based reliability remained 100% at 1–5 m, decreased to 99% at 10 m and 97% at 15 m, and reached 92% at 20 m. Mean command-response latency increased from 88 to 248 ms while RSSI declined from ?38 to ?77 dBm. The main contribution is a reproducible, low-cost evaluation framework that links interface commands, HTTP communication, wireless quality, and physical motion execution. The results indicate that the platform is appropriate for responsive laboratory teleoperation within 15 m, while operation near 20 m requires stronger fail-safe and acknowledgement mechanisms.